DISTRIBUSI PENDAPATAN PETANI CENGKEH DI DESA OTVAI KECAMATAN ALOR BARAT LAUT - Didiana Yanuarita Molebila (Politeknik Pertanian Negeri Kupang, 2022)
The purpose of this study was to determine the level of even distribution and the level of equity of clove farmers' income in Otvai Village, Northwest Alor District, based on the Gini Ratio. Collecting data using survey methods and questionnaires. The focus of the data is on mapping the total income and household income of clove farmers. Data were analyzed by income distribution analysis. The results showed that clove farmers in Otvai village spent a total cost of Rp. 925,939 per harvest, with a total revenue Rp. 5,327,727 per farmer from a total production of 115.71 kg. Thus, the income of each clove farmer reaches Rp. 4,401,788. Based on the mapping and distribution analysis, the income of clove farmers in Otvai village is classified as low evenness level (GC 0.5), where 40% of farm households have clove income < Rp. 1,320,536.Keywords: Evenness level, Clove, Otvai